Aberrant Autophagy Impacts Growth and Multicellular Development in a Dictyostelium Knockout Model of CLN5 Disease - McLaren, Meagan D.; Mathavarajah, Sabateeshan; Kim, William D.; Yap, Shyong Q.; Huber, Robert J. (Frontiers in Cell and Developmental Biology, 2021)
Mutations in CLN5 cause a subtype of neuronal ceroid lipofuscinosis (NCL) called CLN5 disease. While the precise role of CLN5 in NCL pathogenesis is not known, recent work revealed that the protein has glycoside hydrolase activity. Previous work on the Dictyostelium discoideum homolog of human CLN5, Cln5, revealed its secretion during the early stages of development and its role in regulating cell adhesion and cAMP-mediated chemotaxis. Here, we used Dictyostelium to examine the effect of cln5-deficiency on various growth and developmental processes during the life cycle. During growth, cln5- cells displayed reduced cell proliferation, cytokinesis, viability, and folic acid-mediated chemotaxis. In addition, the growth of cln5- cells was severely impaired in nutrient-limiting media. Based on these findings, we assessed autophagic flux in growth-phase cells and observed that loss of cln5 increased the number of autophagosomes suggesting that the basal level of autophagy was increased in cln5- cells. Similarly, loss of cln5 increased the amounts of ubiquitin-positive proteins. During the early stages of multicellular development, the aggregation of cln5- cells was delayed and loss of the autophagy genes, atg1 and atg9, reduced the extracellular amount of Cln5. We also observed an increased amount of intracellular Cln5 in cells lacking the Dictyostelium homolog of the human glycoside hydrolase, hexosaminidase A (HEXA), further supporting the glycoside hydrolase activity of Cln5. This observation was also supported by our finding that CLN5 and HEXA expression are highly correlated in human tissues. Following mound formation, cln5- development was precocious and loss of cln5 affected spore morphology, germination, and viability. When cln5- cells were developed in the presence of the autophagy inhibitor ammonium chloride, the formation of multicellular structures was impaired, and the size of cln5- slugs was reduced relative to WT slugs. These results, coupled with the aberrant autophagic flux observed in cln5- cells during growth, support a role for Cln5 in autophagy during the Dictyostelium life cycle. In total, this study highlights the multifaceted role of Cln5 in Dictyostelium and provides novel insight into the pathological mechanisms that may underlie CLN5 disease.